(untitled) - Nunan, David (New York, 1998)
Comprising a general ELT methodology for ELT teachers, this work covers the development of listening, speaking, writing and reading skills, as well as grammar, vocabulary and pronunciation. Also discussed are classroom management, materials development and learning strategies.
Keywords: Language and languages,Ngôn ngữ và những ngôn ngữ; Study and teaching,Dạy và học